POROUS SILICAS FROM MIXTURES OF Na₂Si₃O₇ AQUEOUS SOLUTION AND TEOS. INFLUENCE OF SODIUM SILICATE AMOUNT - PICIORUS, Elena-Mirela; SVERA (IANASI), Paula; IANASI, Catalin (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Silicon-based mesoporous materials have become increasingly used in various fields as industry, medicine, environment, etc. We developed five samples in mild conditions, at room temperature, of mesoporous silica by substituting tetra-ethyl-orthosilicate (TEOS) with different amount of sodium silicate (Na₂Si₃O₇) precursor by maintaining the total ratio for SiO₂ at 1.8g. Acetic acid (CH₃COOH)/hydrochloric acid (HCl) aqueous solution was used as catalyst keeping the pH at 5. The samples were examined by FT-IR, Raman Spectroscopy, Scanning Laser Confocal Microscopy and Nitrogen Adsorption-Desorption Isotherms. The results indicate enhancements when Na₂Si₃O₇ was added. Sample with TEOS and lowest amount of Na₂Si₃O₇ displayed the best surface area value (750 m²/g) and total pore volume (0.63 cm³/g). Highest amount of Na₂Si₃O₇ in the sample (P5) has considerably influenced the roughness of the material.